Abdominal Massage Decreases Food Intake and Body Weight in High-Fat Diet-Induced Obese Rats Through Upregulating GPR41/GPR43-PYY/GLP-1 Axis - Ma F; Li H; Huang C; Shuai C; An C; Zhang W (Diabetes, Metabolic Syndrome and Obesity, 2025)
Fei Ma,1,* Huanan Li,2,* Caiyin Huang,2 Chenghao Shuai,2 Chengfei An,2 Wei Zhang2 1Tianjin Academy of Traditional Chinese Medicine Affiliated Hospital, Tianjin, 300120, People’s Republic of China; 2Department of Tuina, First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, 300000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei Ma, Tianjin Academy of Traditional Chinese Medicine Affiliated Hospital, Hongqiao District, Tianjin, 300120, People’s Republic of China, Tel +86 022 27345050, Email mf18920580868@163.comBackground: Abdominal massage has been found to exert an important role in helping people in overcoming obesity. However, the mechanism by which abdominal massage induces weight loss remains largely unclear.Methods: Healthy male Sprague-Dawley (SD) rats were randomly grouped into standard diet control (15% fat content) group and high-fat diet (HFD, 40% fat content) group. After 6 weeks of high-fat feeding, rats in the HFD group were successfully modeled, and then separated into the HFD group and HFD plus abdominal massage group. Rats in the HFD plus abdominal massage group were then subjected to abdominal massage for 12 continuous days.Results: Compared to the HFD group, abdominal massage could decrease body weight, food intake and abdominal fat index (AFI) of HFD-fed rats. Meanwhile, compared to the HFD group, abdominal massage obviously attenuated mucosal epithelial damage and reduced inflammatory cell infiltration in colon mucosal tissues of HFD-fed rats. Furthermore, compared to the HFD group, abdominal massage significantly increased GPR42 and GPR43 levels in the colon tissues of HFD-fed rats, and upregulated the production of glucagon-like peptide-1 (GLP-1) and peptide YY (PYY) in colon mucosal tissues of HFD-fed rats.Conclusion: Collectively, abdominal massage could decrease food intake and body weight in HFD-induced obese rats through upregulating GPR41/GPR43-PYY/GLP-1 axis.Keywords: abdominal nudging, obesity, SCFAs, GLP-1, PYY, food intake, body weight